Revolutionizing English Learning with AI: Insights from ChatGPT and Google Gemini - Fitria, Tira Nur (Institut Teknologi Bisnis AAS Indonesia, 2025)
This research describes the use of both Google Gemini and ChatGPT in English language learning. This research is descriptive qualitative. The analysis shows that both ChatGPT and Gemini provide valuable insights into AI's role in English language learning, though their approaches differ. ChatGPT focuses on practical applications like personalized feedback, chatbots, and analytics tools, emphasizing text generation and teacher workload reduction. Google Gemini, with its multimodal capabilities, highlights interactive learning systems, automation, and accessibility improvements in education. Both models stress personalization, interactivity, and teaching efficiency but with different emphases—ChatGPT on student analysis, Gemini on immersive experiences, and data-driven teaching. While both tools offer great potential, the choice between them depends on whether we prioritize text-based tasks (ChatGPT) or multimedia content (Google Gemini). Choosing between ChatGPT and Google Gemini depends on our specific needs. If we require text generation, such as creating articles or engaging in text-based conversations, ChatGPT is a better fit due to its focus on producing natural, relevant text. However, if you need to handle multiple types of data like text, images, audio, and video, Google Gemini's multimodal capabilities make it more versatile for multimedia tasks. While ChatGPT is ideal for text-based applications and integrates easily through APIs, Gemini is more suited for users within the Google ecosystem. ChatGPT is known for generating high-quality text, while Gemini provides good quality across various formats, but its effectiveness varies with context. Ultimately, the best choice depends on whether your focus is on text or multimedia tasks.